Gender bias in Brazil\'s response to covid-19: evaluating the reception of WHO/PAHO recommendations - Pereira, Cristiane Ribeiro (2023)
Here, we present a comprehensive analysis investigating the potential gender bias in global and Brazilian responses to the covid-19 pandemic. Our primary objective was to evaluate the extent to which the World Health Organization (WHO) and the Pan American Health Organization (PAHO) considered the needs and perspectives of women in their key recommendations. Additionally, we aimed to determine the level of adherence of the Brazilian public authorities to these recommendations. Drawing upon insights from feminist literature on Global Health, we have identified relevant topics and intersectional considerations that inform our analysis of the recommendations provided by international organisations (IOs) and subsequent public policies. By employing content analysis techniques, we describe the recommendations issued by WHO/PAHO throughout 2020, along with an examination of the actions taken by the Brazilian executive branch. In the later stages of our research, we prioritised the triangulation of various documents and information complemented by semi-structured interviews. This approach enabled us to select pertinent evidence that effectively addressed our central question regarding gender bias.